A high spatial-temporal resolution emission inventory of multi-type air pollutants for Wuxi city. (20th August 2019) - Hua, Hui; Jiang, Songyan; Sheng, Hu; Zhang, You; Liu, Xuewei; Zhang, Ling; Yuan, Zengwei; Chen, Tianming
Abstract: Currently, atmospheric emission inventory that includes multi-type pollutants and sources is still limited at the city level. This study developed a high-resolution emission inventory of eight pollutants based on detailed investigated data for Wuxi city in 2015. Results show that the total emissions of sulfur dioxide (SO2 ), nitrogen oxides (NOx ), total suspended particulates (TSP), particulate matter with an aerodynamic diameter of 10 μm or less (PM10 ), particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5 ), carbon monoxide (CO), ammonia (NH3 ), and volatile organic compounds (VOCs) were 36.9 kt, 95.2 kt, 287.3 kt, 127.8 kt, 46.0 kt, 626.4 kt, 10.9 kt, and 104.9 kt, respectively. Power plants were the major contributors of SO2 and NOx, accounting for 34.6% and 36.3% of the total emissions, respectively. Road dust was the dominant source of particulate matter, contributing 63.1%, 57.8% and 38.2% to the total TSP, PM10 and PM2.5 emissions, respectively. Around 67.0% of CO emissions were from iron and steel plants, while 50.1% of NH3 emissions were from livestock and poultry sectors. VOCs emissions largely came from oil refinery and chemical industry, with a share of 41.3%. High NH3 emissions were found in the southwest and northeast of Wuxi where high-intensity agriculture was located, while other pollutants were mainly concentrated on the eastern Wuxi where heavy industries, crowded traffic and highly dense population were located. Most pollutants from the industrial source exhibited the lowest value in February due to the Chinese Spring Festival with the exception of CO and NH3 . This study helps to formulate the targeted air pollution control measures for Wuxi city by providing detailed information regarding the spatial-temporal distribution of multi-type air pollutants. Graphical abstract: Image 1 Highlights: A high-resolution emission inventory was established for Wuxi in 2015. Eight conventional air pollutants were estimated based on local investigated data. Industry, agriculture and fugitive dust were the main sources of air emissions. High emissions were around the populous east areas with heavy industry and traffic.